Strategic Knowledge Management Framework For Technology Transfer In Indonesian Joint Operation Construction Projects - Suryana, Yudha Trimuliadi; Rarasati, Ayomi Dita (CSID Journal of Infrastructure Development, 2024)
Joint Operation (JO) construction companies in Indonesia face persistent challenges in technology transfer, including misalignment between advanced technologies and organizational capacities. Knowledge management has been proposed as a strategic solution, but its implementation remains underdeveloped. This study develops a framework to enhance technology transfer in JO construction projects through improved knowledge management practices. Utilizing a mixed-methods approach, the research combines a literature review with an analytical hierarchy process, fuzzy set theory, and a simple additive weighting method, supported by data from selected respondents involved in the Jakarta Mass Rapid Transit (MRT) project (CP201). Key findings identify knowledge acquisition, utilization, and sharing as critical processes, with sub-criteria such as clarity of roles and responsibilities and external collaboration emerging as pivotal. The SECI (Socialization, Externalization, Combination, and Internalization) model is applied to guide the development of actionable strategies for effective knowledge management. This study contributes a tailored framework for Indonesian JO construction companies, bridging gaps in technology transfer and advancing organizational capabilities. Practical recommendations are provided to improve knowledge integration and foster sustainable growth in infrastructure projects.